The snow must go on: how German cross-country skiers maintained training and performance in the face of COVID-19 lockdowns - Kock, H.; Schürer, A.; Staunton, C. A.; Hanstock, H. G. (Frontiers in Sports and Active Living, 2024)
Background: The Covid-19 pandemic in 2020 led to disruption of sporting events, with athletes obliged to comply with national lockdown restrictions.